2017
DOI: 10.1002/jez.2066
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Preference and Sex Differentiation in African Catfish, Clarias gariepinus

Abstract: The African catfish Clarias gariepinus has a genetic sex determination system in which high temperature induces masculinization. The thermosensitive period for sex differentiation is short and occurs very early (from 6 to 8 days posthatching [dph]). As young juveniles can encounter high masculinizing temperature (36.5°C) in African water points, we aimed to determine the thermal preference of sexually undifferentiated juveniles and investigate if they spontaneously move toward high masculinizing temperature. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…niloticus ) 40 hours after transfer into a multichamber device (control at 26.50 ±0.33°C) with a homogeneous distribution occurring throughout the chambers. A previous study using African catfish ( Clarias gariepinus ) in the same device (step temperature gradient continuum with 3 compartments) similarly showed that undifferentiated juveniles spread nearly evenly across the control continuum during the 12 days of the experiment [29]. Other studies conducted on adult zebrafish ( Danio rerio ) also reported an almost random distribution among chambers [30,31].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…niloticus ) 40 hours after transfer into a multichamber device (control at 26.50 ±0.33°C) with a homogeneous distribution occurring throughout the chambers. A previous study using African catfish ( Clarias gariepinus ) in the same device (step temperature gradient continuum with 3 compartments) similarly showed that undifferentiated juveniles spread nearly evenly across the control continuum during the 12 days of the experiment [29]. Other studies conducted on adult zebrafish ( Danio rerio ) also reported an almost random distribution among chambers [30,31].…”
Section: Discussionmentioning
confidence: 84%
“…niloticus juveniles would spontaneously move to high, potentially masculinizing temperatures, inducing sex reversal. The thermal preference of species exhibiting a GSD + TE sex determining system during the thermosensitive period for sex determination has only been studied in African catfish ( Clarias gariepinus ) [22]. These authors showed that undifferentiated juveniles migrated to high temperatures during the critical period of sex determination (6 to 8 days post hatching), inducing skewed sex ratios toward males (from 78 to 93%).…”
Section: Introductionmentioning
confidence: 99%
“…Santi et al (2016) demonstrated that C. gariepinus displayed thermo sensitivity in the sex differentiation process, with a masculizing effect at high temperature, with a sex ratio skewed towards the male phenotype. Santi et al (2017) also reported that C. gariepinus has a genetic sex determination system in which high temperature induces masculinization. The temperature values during the period of study were 27.37 ± 0.03°C in the first year and 27.36 ± 0.03°C in the second year, with no significant difference in the means of the two years (P = 0.083) (Ajala and Fawole, 2016a).…”
Section: Discussionmentioning
confidence: 93%
“…Equally important, the highly thermosensitive period is short and extends from 6 to 8 dph, long before the appearance of the first histological signs of sex differentiation at 25 dph. When applied during this period, high temperature frequently masculinized progenies up to 80-100% (Santi et al, 2017(Santi et al, , 2016. We focused the present study on the period before (0 hpf) until shortly after (14 dpf) the highly thermosensitive period, because in African catfish, some progenies were not thermosensitive after 14 dph (Santi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%